Development of new voltammetric sensing systems and analytical mehods as applied to flow injection liquid charomatography and microchip capillary electrophoresis - Weena Siangproh (Chulalongkorn University, 2014)
Thesis (Ph.D.)--Chulalongkorn University, 2006